2017
DOI: 10.1063/1.4996373
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature synthesis of highly oriented p-type Si1-xGex (x: 0–1) on an insulator by Al-induced layer exchange

Abstract: A composition tunable Si 1-x Ge x alloy has a wide range of applications, including in electronic and photonic devices. We investigate the Al-induced layer exchange (ALILE) growth of amorphous Si 1-x Ge x on an insulator. The ALILE allowed Si 1-x Ge x to be large grained (> 50 lm) and highly (111)-oriented (> 95%) over the whole composition range by controlling the growth temperature (400 C). From a comparison with conventional solid-phase crystallization, we determined that such characteristics of the ALILE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Metal-induced layer exchange (MILE) has been actively studied in the field of group-IV semiconductors, including Si 2731 , Ge 3237 , and SiGe 38,39 . In MILE, an amorphous semiconductor layer crystallizes through “layer exchange” between the amorphous layer and a catalyst metal layer.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-induced layer exchange (MILE) has been actively studied in the field of group-IV semiconductors, including Si 2731 , Ge 3237 , and SiGe 38,39 . In MILE, an amorphous semiconductor layer crystallizes through “layer exchange” between the amorphous layer and a catalyst metal layer.…”
Section: Introductionmentioning
confidence: 99%
“…20 This is attributed to the difference in the activation energies of Si and Ge required for nucleation and growth. 21,30 Here, we observed that large grains can be obtained even for Ge-rich SiGe by controlling Td. The window at which Td has an effect of increasing the grain size narrows as x increases, though x = 0.1 does not follow this trend.…”
Section: Resultsmentioning
confidence: 66%
“…11,12 A large number of SGOI-forming methods have been developed: layer transfer, 13 Ge condensation, 4,[14][15][16] laser annealing, 7,10 rapid-melting growth, 8,12 chemical-vapor deposition (CVD), 2,17,18 sputtering, 9 solid-phase crystallization (SPC), 3,[19][20][21][22] and metal-induced crystallization 23,24 including layer exchange. [25][26][27][28][29][30] Despite the variety of methodologies, it is still difficult to obtain a large-area SGOI with excellent crystallinity and electrical characteristics by a simple method, suitable for practical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, the low-temperature synthesis of polycrystalline (poly-) Ge on glass has been investigated using solid-phase crystallization (SPC) [9][10][11], sputtering [12], and chemical vapor deposition (CVD) [13,14]. Metal-induced layer exchange, using Al [15][16][17][18][19], Au [20,21], and Ag [22,23] as catalysts, is a unique method that significantly lowers the crystallization temperature of amorphous (a-) Ge (≤ 350 °C). In particular, Al-induced layer exchange (ALILE) allows for large-grained (> 50 µm), (111)-oriented, and highly p-doped Ge thin films (thickness: 50 nm) [18,19], which will be useful as a seed layer for a thick (> 500 nm) light absorbing layer.…”
Section: Introductionmentioning
confidence: 99%